Stereotactic Body Radiotherapy for Large Unresectable Hepatocellular Carcinomas – A Single Institution Phase II Study. Issue 7 (July 2020) - Beaton, L.; Dunne, E.M.; Yeung, R.; Rackley, T.; Weber, B.; Mar, C.; Yong-Hing, C.J.; Yoshida, E.M.; DeVries, K.; Lee, R.; Duzenli, C.; Loewen, S.K.; et al.
Abstract: Aims: To evaluate the safety and efficacy of liver stereotactic body radiotherapy (SBRT) in the treatment of unresectable hepatocellular carcinomas (HCC) measuring >5 cm. Materials and methods: Between November 2013 and February 2016, 13 patients with unresectable HCC (>5 cm), ineligible for other local treatments, with a Child-Pugh score (CPS) ≤ B7, were enrolled into a single-institution phase II study. SBRT was delivered by volumetric-modulated arc radiotherapy. Radiological response was reported using modified Response Evaluation Criteria in Solid Tumours criteria and toxicities graded by Common Terminology Criteria for Adverse Events v4 criteria. Results: Sixteen hepatomas (median size 7.5 cm, range 5.1–9.7 cm) were treated in 13 patients. The baseline CPS was A5/6 in nine patients (69%) and B7 in four patients (31%). Five patients (38%) received previous liver-directed treatment. The median prescribed dose was 45 Gy (range 40–45 Gy) in five fractions. The median follow-up was 17.7 months. The 1-year local control rate was 92%. The median overall survival was 17.7 months and the 1-year overall survival was 62%. The median time to local progression was not reached. Five patients (39%) had an increase in CPS by two or more points at 3 months. Overall, there were 10 grade 3 acute toxicities occurring in seven patients, of which six were haematological. Quality of life remained clinically stable or improved at 3 months in 61.5% and 53.8% of patients based on the European Organisation for Research and Treatment of Cancer Quality of Life Questionnaire Core-30 Global Health Score and Functional Assessment of Cancer Therapy – Hepatobiliary version 4 score, respectively. Conclusions: In our cohort, SBRT to unresectable large HCC tumours provided excellent local control with acceptable toxicities. Regional recurrence remained the major cause of failure. Further studies are warranted to examine the role for SBRT in combination with other modalities to maximise disease control in the liver. Highlights: SBRT is a safe and effective treatment for large unresectable HCCs >5 cm. SBRT can be delivered safely even after previous liver-directed therapies. SBRT provides excellent local control with control rates of 92% at 1 year. SBRT for large unresectable HCCs provides a median overall surviva1 of 17.7 months.